2006
DOI: 10.1002/pmic.200500220
|View full text |Cite
|
Sign up to set email alerts
|

Array based capillary IEF with a whole column image of laser‐induced fluorescence in coupling to capillary RPLC as a comprehensive 2‐D separation system for proteome analysis

Abstract: Based on array CIEF (ACIEF) and a novel whole column imaging detection (WCID), a comprehensive 2-D system with laser-induced fluorescence was developed for protein mapping. By coupling capillary RPLC (CRPLC) as the first dimension and ACIEF as the second dimension, a high-throughput and high-resolution proteomic expression profiling was obtained. An array of up to 60 capillaries was assembled, with electrical connections made through filling small breaks, created on each capillary at positions of buffer reserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 33 publications
0
19
0
1
Order By: Relevance
“…Based on our previous studies [19,20], the objective of this work was to develop an effective multidimensional fractionation and separation procedure that could be combined with MS to identify proteins within complex mixtures. First, the feasibility of the 2-D liquid-based protein fractionation strategy utilizing cRPLC and coupled to CIEF separation was tested with a mixture of four model proteins with different pIs and molecular masses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our previous studies [19,20], the objective of this work was to develop an effective multidimensional fractionation and separation procedure that could be combined with MS to identify proteins within complex mixtures. First, the feasibility of the 2-D liquid-based protein fractionation strategy utilizing cRPLC and coupled to CIEF separation was tested with a mixture of four model proteins with different pIs and molecular masses.…”
Section: Resultsmentioning
confidence: 99%
“…A 2-D separation system, coupling capillary RP LC (cRPLC) to CIEF, has been developed for protein and peptide mapping by our group [19,20]. RP LC and CIEF are both high-efficiency separation technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al reported the development of PCAS (ProteinCentric Annotation System) as an online resource of pre-computed proteome annotation data; PCAS gives better annotation coverage for model proteomes by employing a wider collection of available algorithms [98] . Based on array CIEF (ACIEF) and a novel whole column imaging detection (WCID), Mao et al proposed a comprehensive 2D system with laser-induced fluorescence for protein mapping [99] .…”
Section: Proteomicsmentioning
confidence: 99%
“…Because cRPLC has an orthogonal separation mechanism to CIEF, the 2-D system provides high-resolution separation for proteins, with a peak capacity of more than 10 000. Recently, cRPLC (first dimension) coupled to an array CIEF (second dimension) with a novel WCID has been developed for peptide mapping [250]. An array of up to 60 capillaries was assembled in the system, allowing quantitative detection of thousands of focusing protein bands.…”
Section: Lc-cementioning
confidence: 99%